Tuning ground state degeneracy and quantum criticality in Ce1-xLaxTiGe - Sereni, Julian Gustavo Renzo (2010)
We have tuned the paramagnetic heavy Fermion (HF) system CeTiGe to a more magnetic state and toward quantum criticality (QC) by partially substituting La for Ce. The induced volume expansion leads to a pronounced decrease of the Kondo temperature (TK), from ≈50 K in pure CeTiGe to less than 4 K at large La content. Since the former value is of the order of the crystal field splitting, while the latter is well below, the systems evolves from a large degeneracy equation image Kondo system at equation image to a conventional equation image Kondo system at equation image. There, the first excited crystal field doublets become apparent in the T dependence of the specific heat CP(T) at an excitation energy equation image. The reduction of the degeneracy is expected to enhance the decrease of TK, explaining the strong reduction by more than one order of magnitude observed in this system. The decrease of TK drives the system toward QC as evidenced by a divergence of CP(T)/T and χ(T) toward low temperatures in the equation image sample.